A functional menadione biosynthesis pathway is required for capsule production by Staphylococcus aureus. Issue 11 (26th November 2021) - Altwiley, Dina; Brignoli, Tarcisio; Edwards, Andrew; Recker, Mario; Lee, Jean C.; Massey, Ruth C.
Abstract : Staphylococcus aureus is a major human pathogen that utilises a wide array of pathogenic and immune evasion strategies to cause disease. One immune evasion strategy, common to many bacterial pathogens, is the ability of S. aureus to produce a capsule that protects the bacteria from several aspects of the human immune system. To identify novel regulators of capsule production by S. aureus, we applied a genome wide association study (GWAS) to a collection of 300 bacteraemia isolates that represent the two major MRSA clones in UK and Irish hospitals: CC22 and CC30. One of the loci associated with capsule production, the menD gene, encodes an enzyme critical to the biosynthesis of menadione. Mutations in this gene that result in menadione auxotrophy induce the slow growing small-colony variant (SCV) form of S. aureus often associated with chronic infections due to their increased resistance to antibiotics and ability to survive inside phagocytes. Utilising such an SCV, we functionally verified this association between menD and capsule production. Although the clinical isolates with polymorphisms in the menD gene in our collections had no apparent growth defects, they were more resistant to gentamicin when compared to those with the wild-type menD gene. Our work suggests that menadione is involved in the production of the S. aureus capsule, and that amongst clinical isolates polymorphisms exist in the menD gene that confer the characteristic increased gentamicin resistance, but not the major growth defect associated with SCV phenotype.